The impact of conservation agriculture adoption on farmer welfare : a comparative assessment of Kenya and Tanzania - Mungatana, Eric D. (University of Pretoria, 2021)
Mini Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2021.